The Impacts of Modern Information Technology in Learning Tamil - Raguram, S. (My University, 2008)
Learning a language is a unique process compared to learning other subjects, and it needs complete emotional participation and coherent attention. The impact created by modern information technology in the learning of the Tamil Language is immense. It helps the students to come out of traditional classroom learning and rigid limits and makes the self-learning without any boredom possible and helps to develop listening, reading, speaking and writing skills of this language. Modern information technology facilitated knowing the cultural and linguistic dimensions of the language. Online learning helps the learners to refer to as many sources from different parts of the world. The Tamil software helps very much to the learners. Multimedia learning helps us to learn the three elements of the Tamil Language; performance, music and drama. Electronic documentation and online conferences enabled by cutting-edge technology help us to learn and comment in real-time. The new digital learning provides a learning environment with harmony and interest. Modern Information Communication and Technology made it possible to learn all the other technologies in Tamil Language and also facilitated the learning of the Tamil Language.
Keywords: Information Technology; Tamil Language; Learning Tamil